Frieren : beyond journey's end. Volume 1 - Yamada, Kanehito (VIZ Media, LLC, 2021)
The adventure is over but life goes on for an elf mage just beginning to learn what living is all about. Elf mage Frieren and her courageous fellow adventurers have defeated the Demon King and brought peace to the land. With the great struggle over, they all go their separate ways to live a quiet life. But as an elf, Frieren, nearly immortal, will long outlive the rest of her former party. How will she come to terms with the mortality of her friends? How can she find fulfillment in her own life, and can she learn to understand what life means to the humans around her? Frieren begins a new journey to find the answer. Frieren, Himmel, Heiter and Eisen celebrate their victory by watching the Era meteor shower, an event which occurs every 50 years. After casually promising to meet them when it happens again, Frieren leaves to study magic. The years go by and the day comes when Frieren must attend the funeral of one of her comrades, confronting her with her own near immortality. When she realizes she barely knew the man she fought beside for ten years, she sets out to learn more about people, and carry out the last wishes of her friend--to decipher the secret magic of immortality.